Analisis kecemasan dalam pembelajaran senam lantai roll depan peserta didik kelas XI SMAN 2 labuapi - Nadia Aulia Rizki; Susi Yundarwati; Sekar Pudak Wangi (Yayasan Baru Haji Samsudin, 2025)
The problem in this study is the anxiety of students before the front roll floor gymnastics movement and it is difficult to learn about excessive difficulties that can have a negative impact on students because it can reduce the quality oflearning. The purpose of this study was to determine the anxiety of students. Thisresearch method is a quantitative description. The subjects of this study werestudents of class XI SMAN 2 Labuapi. The data analysis technique used in thisstudy was descriptive analysis with descriptive statistical methods and to analyzestudent anxiety, researchers conducted data analysis to find the frequency value of student anxiety, with mean, median, minimum and maximum values processed through the SSPS application. Based on the results of the study of anxiety inlearning front roll floor gymnastics of class XI students of SMAN 2 Labuapi, itshows that students experience anxiety in learning front roll floor gymnastics by79.3%. The anxiety experienced by students during learning front roll floorgymnastics is due to psychological factors by 72.4%.